Passage of current in needle telegraph system - Ward, Lock (Wonders of electricity and the elements, being a popular account of modern electrical and magnetic discoveries, magnetism and electric machines, the electric telegraph and the electric light, and the metal bases, salt, and acids, 1870)
Diagram depicting the passage of current in a needle telegraph system. One of the two main types of electromagnetic telegraphs, needle telegraphs use indicating needles moved electromagnetically as a means of displaying messages.
Keywords: Electricity; Magnetism; Electric machines; Telegraph; Scientific illustration; Communication and technology; Telecommunication